Seen but not Heard The Significance of the Mute Child Character, Astyanax, in Euripides’ Trojan Women - Moller, Olivia Katelyn (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.